EATING PRACTICES OF FAMILY FARMERS IN THE MUNICIPALITY OF PETRÓPOLIS-RJ, BRAZIL - Nichole Ramos da Silva; Aline Gaudard e Silva de Oliveira (Universidade do Estado do Rio de Janeiro, 2018)
Objective: To identify healthy and unhealthy eating practices and habits of family farmers in the Caxambu district, in the city of Petrópolis-RJ, Brazil. Methodology: This is a cross-sectional study with a sample of 35 family farmers. Information was obtained through interviews, using a structured and standardized questionnaire. Eating practices were evaluated from the items of the questionnaire used by SISVAN associated to the frequencies of consumption of the questionnaire used by VIGITEL. Results and Discussion: The consumption of healthy foods (fruits, vegetables and greens), with the exception of beans, was low, and the consumption of unhealthy foods was considerably high when compared to other studies. In addition, almost half of the interviewed farmers have the habit of eating meals while watching TV, using their cell phones and/or computers, which is considered a risky behavior for the development of obesity. Conclusions: The eating practices of the family farmers of Caxambu deserve attention, for despite the easy access to healthy foods, it was found a low intake of fruits, vegetables and greens, and a high consumption of unhealthy foods, such as sweetened beverages and processed meats. There is evidence of the need to carry out actions aimed at improving the eating profile, the health and the quality of life of family farmers. DOI: 10.12957/demetra.2018.34989